Emotional changes of patients undergoing maintenance hemodialysis during the COVID-19 lockdown - Qianyun Zhao; Yuyu Zhu; Junyi Jiang; Deguang Wang (Annals of Medicine, 2025)
Objective This study aims to investigate the influence of the COVID-19 lockdown period on anxiety, anger, loneliness and depression, four categories of negative emotions, in patients undergoing maintenance hemodialysis.Methods A cross-sectional survey was conducted, and a total of 174 patients receiving maintenance hemodialysis at the Second Affiliated Hospital and Fourth Affiliated Hospital Hemodialysis Center of Anhui Medical University between October 20 and October 27, 2022, were selected as the study subjects. We used the Medical Staff Stress and Negative Emotions Scale (MSSNS) to assess the emotional changes in anxiety, anger, loneliness and depression in these patients before and during the lockdown.Results A total of 174 questionnaires were collected, all of which were valid. During the lockdown period, the scores for anxiety (18.89 ± 6.83), anger (10.20 ± 3.32), loneliness (10.86 ± 3.81) and depression (14.13 ± 4.24) were significantly higher than the scores before the lockdown for anxiety (16.63 ± 4.64), anger (9.74 ± 2.60), loneliness (10.26 ± 3.35) and depression (13.11 ± 4.24). These differences were statistically significant (p < 0.001).Conclusion During the COVID-19 lockdown, patients undergoing maintenance hemodialysis experienced significantly higher levels of anxiety, anger, loneliness and depression compared to the pre-lockdown period. Our study emphasizes the importance of paying sufficient attention to the mental health of hemodialysis patients during such public health crises.